ASSESSING BORDER SHOPPER’S MOTIVATION AT PADANG BESAR, PERLIS - Rafie, Mahirah; Omar, Shida Irwana; Adnan, Syuhada Farhana (PLANNING MALAYSIA, 2021)
Shopping tourism had evolved over the years in becoming the main generator for the tourism industry, especially in Malaysia border areas like Padang Besar, Perlis. Even though there are carrying capacity issues and inadequate facilities, people continue to visit Padang Besar, especially during weekends and public holidays. Accordingly, this study investigates shopper motivation factors to shop at Padang Besar. The findings indicated that four push motivation factors and six pull motivation factors were important. Three categories of shoppers were identified from these factors, namely: the hunter shopper, prudent shopper, and comfortable shopper. The contribution of this study also presents a holistic view of border shoppers and various types of shoppers who visit Padang Besar, thereby helping stakeholders obtain valuable information to implement strategies for developing this area as a border shopping destination. It is anticipated that this study’s results will help improve Padang Besar’s development in building good facilities and infrastructure as demanded by visitors.